Computer-Controlled Scanning Electron Microscopy Investigation on Transformation of Minerals and PM2.5 Emissions During Chinese Coal Combustion - Ji, Mingjun; Dong, Zhongbin; Li, Hanxu; Wang, Qunying; Ninomiya, Yoshihiko (Asian Journal of Chemistry, 2013)
The mineralogy of two coals and its combustion-generated particulate matter (PM2.5) was characterized in detail by computer controlled scanning electron microscopy. The results show that the interactions among minerals plays an important role in the PM2.5 formation. Transformations of fine Si-Al mineral grains provided by the minerals in coal HT into coarse particles are responsible for the reduction of PM2.5 during the combustion of coal HT. The transformed fine Si-Al particles are captured by the coarse Ca-Mg-Al-Si provided by the minerals in coal HT to form larger Ca-Mg-Al-Si particles. Increasing Ca and Mg concentration in coal HT enhances the liquid concentration produced during combustion and hence affects the emissions of PM2.5.